Striatal circuits, habits, and implications for obsessive–compulsive disorder. (February 2015) - Burguière, Eric; Monteiro, Patricia; Mallet, Luc; Feng, Guoping; Graybiel, Ann M
Highlights: Involvement of corticostriatal circuits in OCD is receiving strong new experimental support. This evidence is concordant with clinical evidence based on OCD patient studies. Clinical and experimental work further converge on OFC-ACC corticostriatal circuits as critical. Abstract : Increasing evidence implicates abnormalities in corticostriatal circuits in the pathophysiology of obsessive–compulsive disorder (OCD) and OC-spectrum disorders. Parallels between the emergence of repetitive, compulsive behaviors and the acquisition of automated behaviors suggest that the expression of compulsions could in part involve loss of control of such habitual behaviors. The view that striatal circuit dysfunction is involved in OC-spectrum disorders is strengthened by imaging and other evidence in humans, by discovery of genes related to OCD syndromes, and by functional studies in animal models of these disorders. We highlight this growing concordance of work in genetics and neurobiology suggesting that frontostriatal circuits, and their links with basal ganglia, thalamus and brainstem, are promising candidates for therapeutic intervention in OCD.